2005
DOI: 10.1002/bip.20210
|View full text |Cite
|
Sign up to set email alerts
|

Acid–base titration of melanocortin peptides: Evidence of Trp rotational conformers interconversion

Abstract: Tryptophantime-resolved fluorescence was used to monitor acid-base titration properties of alpha-melanocyte stimulating hormone (alpha-MSH) and the biologically more potent analog [Nle4, D-Phe7]alpha -MSH (NDP-MSH), labeled or not with the paramagnetic amino acid probe 2,2,6,6-tetramthylpiperidine-N-oxyl-4-amino-4-carboxylic acid (Toac). Global analysis of fluorescence decay profiles measured in the pH range between 2.0 and 11.0 showed that, for each peptide, the data could be well fitted to three lifetimes wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…6, panel C). It has been proposed that the multi-exponential decay of Trp in peptides and proteins results from the occurrence of different rotamers and that the pre-exponential factors are related to the relative rotamer populations5051. Our observation of changes in pre-exponential factors due to CTX heterodimer formation is then related to the conformational changes affecting the Trp residues.…”
Section: Discussionmentioning
confidence: 62%
“…6, panel C). It has been proposed that the multi-exponential decay of Trp in peptides and proteins results from the occurrence of different rotamers and that the pre-exponential factors are related to the relative rotamer populations5051. Our observation of changes in pre-exponential factors due to CTX heterodimer formation is then related to the conformational changes affecting the Trp residues.…”
Section: Discussionmentioning
confidence: 62%
“…EPR and time-resolved fluorescence were also used to investigate the interaction between the TOAC-labeled peptides and DMPG (Fernandez et al 2005a). EPR spectra showed that both peptides displayed similar, strongly restricted motion, indicating insertion into the membrane, both in the gel and in the liquid crystalline phases.…”
Section: Biologically Active Peptides: Ligands and Fragments Of G Promentioning
confidence: 99%
“…A 10 ns QMD simulation on -melanotropin, using the CHARM M22 all atom force field and a potential of mean force modeling the solvation effects, yielded three 1 rotamers with the gauche + being less populated than the trans and gauchestates [120]. The presence of rotamers was corroborated by tri-exponential fluorescence decay [121,122] and NMR spectra [123]. However, the NMR studies suggested that the Trp9 rotamer populations are predominantly in the trans and gauche -states with the gauche + states being virtually unpopulated.…”
Section: Rotamer Distributionsmentioning
confidence: 90%
“…A deviation from the Boltzmann distribution is expected to increase with molecule size. Interestingly, while the short fluorescence lifetime component, ascribed to the gauche + state, changed little with medium pH, the amplitudes of the intermediate and long lifetime components, assigned to the trans and gauche -states, depended strongly on medium pH between pH 2 and pH 11, indicating rotamer interconversion [121].…”
Section: Rotamer Distributionsmentioning
confidence: 97%